Remote Sensing and GIS for Mitigation System at Merapi Volcano, Central Java, Indonesia - Setianto, Agung (2011)
Several state-of-the-art scientific papers recently demonstrate that remote sensing data collected by different types of satellite and airborne platforms as part of multi temporal remote sensing, in integration with Geographic Information System (GIS) spatial modeling, have a great potential to solve problems in providing near real-time data for monitoring a volcano. For future volcanic hazards, we should have a monitoring mitigation system which is supported by a reliable decision support system that allows scientist and decision makers to evaluate different scenarios quickly during the crisis. Such system will utilize huge data sets from different instrumentation and platforms. Therefore we initiate a research which is aimed to study the integration of of multi data sources within a GIS as s key tool for monitoring system of a volcano. Remote sensing is critical for supplying near real-time data source, but the challenge is to select the most cost-effective one.